Synthesis of 2,3,7-trihydroxy-9-(3,4,5-trimethoxy)- phenylflurone-3 and Its Application to Spectrofluorescence Quenching Determination of Microamounts of Molybdenum in Tobacco - XIE, YUEQIN; YAN, XIANGYANG; TONG, HONGWU; LIU, SHAOMIN (Asian Journal of Chemistry, 2010)
A new fluorescence reagent, namely 2,3,7-trihydroxy-9-(3,4,5-trimethoxy)phenylflurone-3 was synthesized and sensitive method for the spectrofluorescence quenching determination of molybdenum with the fluorescence reagent, in presence of cetyltrimethyl ammonium bromide, is described. In H3PO4 medium, the fluorescence intensity of trimethoxyphenylfluorone is quenched due to formation of complex of molybdenum and trimethoxyphenylfluorone. The detection limit is 1.5 ng mL-1 and linear range is between 2-80 ng mL-1. The proposed method has been applied to the determination of Mo in tobacco.